REKOMENDASI GEOMETRI LERENG PENAMBANGAN OPTIMUM PADA TAMBANG BATUGAMPING PT. CITATIH PUTRA SUKABUMI - Zen, Zainal Abidin; A.A. Inung Arie Adnyano,; Shilvyanora Aprilia Rande, (ReTII, 2021)
Citatih Putra Sukabumi mining limestone using the quarry method. In mine planning quarry method, slope geometry becomes a very important factor to be studied. Slope geometry that is not optimal will have a large enough loss impact for the company, the loss referred to in the form of landslides or the existing resources are not used optimally. The finite element method is the analytical method used in this study, the input data required include the value of cohesion, internal shear angle, rock density, poison ratio, modulus of elasticity and groundwater level. The study conducted on the geometry of the mining slopes of PT. CPS by simulating several variations of slope height and slope, so that the optimal slope geometry is obtained at static FK = 1.1 for single slopes and dynamic FK = 1 for overall slopes. Based on the results of the analysis of the optimum slope geometry on a single slope, it can be seen by the equation y = 0.1845x2 - 5.4139x + 114.94 while for the overall slope with a single slope of 8.10 and 12 meters the equation is y = 0.0061x2 - 0.961x + 89.723 , y = -0.0002x2 - 0.1353x + 64,765 and y = -0.0002x2 - 0.0721x + 57.649 where the value of x is the desired height and y is the optimal angle that can be realized